IMPROVEMENT OF PUBLIC-PRIVATE PARTNERSHIP MECHANISM FOR BETTER IMPLEMENTATION OF SOCIALLY SIGNIFICANT PROJECTS - N. Zolotnikov (Вестник университета)
The article is devoted to problems of effective functioning of an economical and legal form of interaction of the state and business in the form of public-private partnership (PPP). The author proves needs of introduction in the legal framework of the term PPP, and also modification of the regulatory legal acts regulating this type of interaction. It has a new explanation and definition of a concept and function of PPP, offered by the author from public-private and the municipal-private partnership offered in the Federal law of 13.07.2015 No. 224 Federal law. For successful implementation of infrastructure and social megaprojects (in the sphere of transport infrastructure, housing and communal services, ecology, education, health care, etc.) in scales of the state, it is offered to use an advanced method of interaction of a public-public sector in the new form of PPP.